Brain positron emission tomography with 2-18F-2-deoxi-D-glucose of patients with dystonia and essential tremor detects differences between these disorders. Issue 1 (February 2018) - Belenky, Vadim; Stanzhevsky, Andrei; Klicenko, Olga; Skoromets, Alexandr
We studied patients with dystonia (D) and essential tremor (ET) using positron emission tomography (PET) equipped with Cortex ID software. This allowed PET brain visualisation to be compared to scans of a control group by means of the z-score. The study revealed hypo-metabolism in both D and ET groups, and additionally revealed a difference between these two groups of patients in certain areas of the brain. These two nosological forms overlap in clinical features and are difficult to differentiate. The PET picture may help to provide a differential diagnosis in addition to the biochemical difference in dopamine exchange previously revealed by us in this group of patients.